2022
DOI: 10.47672/ejhs.1215
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Practices in Hotels in Central Region, Ghana: Does Being a TVET-Trained Housekeeper Matter?

Abstract: Purpose: Despite evidences that training helps improve health and safety practices in hotels, there is modicum of knowledge of how being a Technical and Vocational Education and Training-trained housekeeper influences health and safety practices in hotels in Central Region, particularly Cape Coast and Elmina. This study, in response to this gap, examined the effect of being a TVET-trained housekeeper on health and safety practices in hotels in Cape Coast and Elmina. Methodology: The explanatory research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Majority (60%) of the subjects worked for 10-12 hours a day, 34% worked for 8-10 hours on an average, , and 6% subjects worked more than 12 hours daily on an average which may be cause of work related injuries. Supporting this study Siaw (2018) reported that as high as (55.5%) housekeepers strongly agreed that working for long hours is a threat to the safety of the housekeepers. For number of rooms being cleaned during the shift majority (46%) of the subjects cleaned 13-15, 39% cleaned 16-18 rooms, and 15% cleaned more than 18 rooms during their work hours.…”
Section: Results and Discussion Sociodemographic Detailssupporting
confidence: 71%
“…Majority (60%) of the subjects worked for 10-12 hours a day, 34% worked for 8-10 hours on an average, , and 6% subjects worked more than 12 hours daily on an average which may be cause of work related injuries. Supporting this study Siaw (2018) reported that as high as (55.5%) housekeepers strongly agreed that working for long hours is a threat to the safety of the housekeepers. For number of rooms being cleaned during the shift majority (46%) of the subjects cleaned 13-15, 39% cleaned 16-18 rooms, and 15% cleaned more than 18 rooms during their work hours.…”
Section: Results and Discussion Sociodemographic Detailssupporting
confidence: 71%
“…In the urban areas, people in the community collect and store waste for a waste collection organization to finally collect them at a fee [ 17 – 19 ]. This way of waste collection is likely to be adopted by the schools in the urban areas [ 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Siaw [ 18 ] asserts that the most common method of solid waste management practice in various senior high schools is dumping in pits. According to Debrah et al [ 6 ], most of the senior high schools dig pits as storage for the waste they generate.…”
Section: Introductionmentioning
confidence: 99%